Current antimicrobial prescription at outpatient dentistry centers and clinics in tertiary-care hospitals in Tokyo, Japan: A multicenter cross-sectional study - Yasuaki Tagashira; Masao Horiuchi; Atsushi Kosaka; Takuya Washino; Mikihiro Horiuchi; Shutaro Murakami; Itoe Tagashira; Hitoshi Honda (Cambridge University Press, 2021)
Abstract Background: Antimicrobial administration is necessary before specific dental procedures to prevent postprocedural infections and complications and antimicrobials are sometimes indicated for the treatment of odontogenic infections. However, antimicrobials are commonly misused by dentists. Methods: This cross-sectional study was conducted at 4 public, tertiary-care hospitals in Tokyo, Japan, from June to July 2019. We included patients who received an antimicrobial prescription at the outpatient dentistry center or clinic at each participating hospital. The indications for antimicrobial prescription were (1) antimicrobial prescriptions for prophylaxis (APPs) or (2) antimicrobial prescriptions for treatment (APTs). Prescribing patterns were described in terms of antimicrobial choice, timing, and dosages for APPs and APTs. Results: During the study period, 1,772 patients received an antimicrobial prescription. Among them 1,439 (81.2%) were APPs and 333 (18.8%) were APTs. The most common aim of APP was to prevent local infections and complications following tooth extraction (n = 1,244, 86.4%). The proportion of appropriate APPs was only 0.8% (12 of 1,439). Among 1,439 total APPs, 171 (11.9%) were unnecessary, 32 (2.2%) were inappropriate, and 1,224 (85.1%) were suboptimal. Whereas 101 (30.3%) of 333 APTs were appropriate, the remaining 97 instances (29.1%) were unnecessary, 86 (26.7%) were inappropriate, and 46 (13.8%) were suboptimal. Conclusion: Inappropriate antimicrobial prescriptions were common among dentists in Japan. Understanding the differences in the current antimicrobial prescribing patterns for prophylaxis and treatment is critically important for implementing an effective antimicrobial stewardship program in dentistry.